Anatoly I. Bykorez (Experimental Oncology, 2014)
October 29, 2014 marks the 80th anniversary of Anatoly I. Bykorez, Doctor of Medical Sciences, Professor, Laureate of the State Award of Ukraine in Science and Technology.